Implementasi Data Mining dengan Metode Algoritma Apriori dalam Menentukan Pola Pembelian Obat Pada Apotik Sehat Sejahtera Tambolaka - Yoram Jefri Bili; Elfira Umar; Paulus Mikku Ate (CV. ITTC INDONESIA, 2024)
Data mining is a process of obtaining useful information from a database warehouse in the form of knowledge. This research analyzes data using data mining and a priori algorithm methods. Data processing system for compliance in determining drug purchasing patterns using rapid miner in the Sumber Sejahtera pharmacy case study. This system was built based on user needs obtained through interview methods and field studies. The test results using the a priori algorithm and the system that was built show that the results have met the needs in determining drug purchasing patterns based on customers' drug purchasing tendencies. Compared with the current system, this performance is shown in the effectiveness of information from the system regarding determining drug purchasing patterns for drug availability and drug layout to make it easier to find out the whereabouts of drugs seen from the 2 drug itemsets.